Grouping Tolerant Level of Cocoa Genotypes Against Pod Rot Disease in Malaysia - Albert Ling Sheng Chang; Suhaida Salleh; Nuraziawati Mat Yazik; Haya Ramba; Ahmad Kamil Mohd Jaaffar (Indonesian Coffee and Cocoa Research Institute, 2020)
Cocoa pod rot disease (CPRD), caused by Phytophthora palmivora, is the main disease that caused major losses in Malaysia. It is important for screening the cocoa genotypes available in Malaysia for their tolerance level against the CPRD. This paper has an objective to select the potential genotypes tolerant to P. palmivora by grouping the cocoa genotypes available in Malaysia based on four tolerant levels such as tolerant, moderately tolerant, moderately susceptible and susceptible. The experiment was carried out at the laboratory of Plant Pathology at the Cocoa Development and Research Centre Jengka, Pahang using the detachedpod test. Isolate of P. palmivora was obtained from a naturally infected cocoa pod in cocoa field at the Cocoa Research and Development Centre Tawau, Sabah,Malaysia then inoculated by a single point on the ridges of pod to 40 mature unripe pods of each tested genotypes. Fifty genotypes were tested in this study.The assessed disease severity was the rate of lesion area development from 1 to 7 days after inoculation and the proportion of pod area infected by CPRD. Thedisease severity was significantly different among tested genotypes showing tolerance variability against CPRD. Four nonlinear models consisted of Monomolecularmodel, Exponential model, Logistic model and Gompertz model were used to fit the proportion pod infection area curve. The best fitted Gompertz model was used in calculated the area under disease progress curve (AUDPC). The variability of both disease severity variables was used to group the genotypes into four tolerant levels using the k-means clustering method with 10 genotypes in group I (torelant), 14 genotypes in group II (moderately tolerant), 13 genotypes in group III (moderately susceptible) and 13 genotypes in group IV(susceptible). Six genotypes in group I, namely MCBC 13, PBC 221, BAL 209, KKM 19, QH 1176 and KKM 22 were identified to have lower disease severity values compared to control tolerant genotype PBC 123 that could be suggested to the farmers to be planted in the field.